2020
DOI: 10.7759/cureus.11126
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Completion Cholecystectomy: An Audit from the Americas Hepato-Pancreato-Biliary Association (AHPBA) Caribbean Chapter

Abstract: Removal of a gallbladder remnant occasionally becomes necessary when retained stones become symptomatic. Although the laparoscopic approach has been described, it is not yet considered the standard of care. We sought to determine the outcomes after completion cholecystectomies in the resource-poor setting within the Caribbean. Methods We carried out an audit of the databases from all hepatobiliary surgeons in the Anglophone Caribbean. We identified all patients who had completion cholecystectomy over the five-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…We also agree with other authors that it is important for the surgeon who wishes to undertake laparoscopic CBD exploration to have a working knowledge of biliary anatomy and variations [10,15], the ability to properly interpret intra-operative cholangiograms [16][17], an armamentarium of different approaches to duct exploration, stone extraction and closure [10,18,19], and the ability to suture laparoscopically [18,19].…”
Section: Discussionsupporting
confidence: 78%
“…We also agree with other authors that it is important for the surgeon who wishes to undertake laparoscopic CBD exploration to have a working knowledge of biliary anatomy and variations [10,15], the ability to properly interpret intra-operative cholangiograms [16][17], an armamentarium of different approaches to duct exploration, stone extraction and closure [10,18,19], and the ability to suture laparoscopically [18,19].…”
Section: Discussionsupporting
confidence: 78%
“…Our CC rate falls within the reported range in the literature which has been shown to be between 1.8% and 8.8% for CC following STC. 6,8 Our findings identified that all CC had a residual gallbladder remnant of at least 2.5 cm, which is longer that what is recommended gallbladder infundibular remnant size after STC (usually <1 cm). 15,20 This emphasizes the importance of performing STC to described standards of removing the entire anterior-lateral walls of the gallbladder down to within 1 cm of the cystic orifice.…”
Section: Discussionmentioning
confidence: 68%
“…Our CC rate falls within the reported range in the literature which has been shown to be between 1.8% and 8.8% for CC following STC. 6,8…”
Section: Discussionmentioning
confidence: 99%
“…report a 0% conversion rate. However, one study included previous tube cholecystostomy in completion cholecystectomy patients, and the majority of patients studied suffered from remnant cystic stump cholecystitis – not a gallbladder remnant 14,24 . All 26 patients in the current study were performed without a conversion and involved a gallbladder remnant.…”
Section: Discussionmentioning
confidence: 99%
“…In previously published laparoscopic completion cholecystectomy case series, conversion rates to open are reported as high as 40%. 14,15,20 14,24 All 26 patients in the current study were performed without a conversion and involved a gallbladder remnant. The ability to perform this procedure in minimally invasive fashion can be expected to confer the same advantages of the minimally invasive approach to cholecystectomy in comparison with an open approach (decreased morbidity, mortality and length of stay).…”
Section: Perioperative Outcomesmentioning
confidence: 99%